Unified energy efficiency in China's coastal areas: A virtual frontier-based global bounded adjusted measure. (10th June 2018) - Qin, Quande; Li, Xin; He, Huangda; Chen, Xiude
Abstract: China's coastal areas account for a large proportion of the country's total energy consumption. It is important to investigate and identify a specific and accurate evaluation of the energy efficiency in China's coastal areas. In this study, a data envelopment analysis (DEA) approach was utilized to evaluate the unified energy efficiency from 2000 to 2014. Both environmental pollutants and greenhouse gases were treated as undesirable outputs. With the global bounded adjusted measure (BAM-G), unified energy efficiency decomposes into production efficiency and emission efficiency. To obtain an accurate ranking, we proposed a novel DEA model (BAM-VF-G) that combines a virtual frontier (VF) and BAM-G. Moreover, we employed a kernel density estimation to analyze the dynamic evolution of unified energy efficiency during the sample period. The results indicated that: 1) Hebei was always the least efficient province during our study period, followed by Guangxi and Shandong. 2) Almost all of the inefficient scores under non-radial BAM-G were smaller than the scores under radial BAM-G. 3) The level of production efficiency in China's coastal areas increased only slightly during the studied period, but the environmental efficiency level significantly increased. 4) There was a widening gap between the high and low energy-efficient regions. Graphical abstract: Image